Coding Telemedicine Visits for Proper Reimbursement - Gross, Gary N. (Curr Allergy Asthma Rep, 2020)
PURPOSE OF REVIEW: Coding for patient visits and monitoring via telehealth have expanded over the past years with a wide acceptance of telemedicine as a consequence of the coronavirus pandemic. Coding topics of interest to the allergist/immunologist in regard to services provided via telemedicine will be of increasing importance in the coming years. RECENT FINDINGS: CPT coding for telephone as well as synchronous face-to-face telehealth visits has changed over the past few years. With the need for distancing and patient protection during the coronavirus pandemic, telehealth services have increased dramatically. The introduction of newer devices to remotely monitor patients will increase and be incorporated into patient care. SUMMARY: This review will summarize current codes available for designating what services have been provided. The area of telemedicine is changing and will continue to evolve as other platforms for visits are designed and other methods of monitoring patients become available. Coding for these services will be an ongoing need for the provider.